1993
DOI: 10.1080/1073161x.1993.10467180
|View full text |Cite
|
Sign up to set email alerts
|

A Cost-Effectiveness Study of Carbon Monoxide Emissions Reduction Utilizing Remote Sensing

Abstract: The cost-effectiveness of identification and repair of vehicles with excessive carbon monoxide emissions was investigated over the 1991-92 winter period in Provo, Utah. This pilot program used on-road remote sensing at two locations to identify repeat gross polluting vehicles. The owners of gross polluters observed at one of the locations were solicited for a free repair program carried out under the direction of the Utah Valley Community College, Auto-Diesel Division. The same two locations were revisited aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 2 publications
0
18
0
Order By: Relevance
“…5 - 6 The remote sensing technique has also been applied successfully to measure vehicle emissions in a tunnel environment.…”
Section: Discussionmentioning
confidence: 99%
“…5 - 6 The remote sensing technique has also been applied successfully to measure vehicle emissions in a tunnel environment.…”
Section: Discussionmentioning
confidence: 99%
“…hard accelerations, heavy loads on steep hills) for well-tuned vehicles, but may occur transiently for malfunctioning vehicles (Black, 1991;Ross, 1994;Ross et al, 1995). A malfunction of either a feedback component or the catalyst causes extremely high emissions that are driver-independent and beyond the scope of this study, but malfunctions have been shown to be an important component in realworld vehicles (Lawson et al, 1990;Bishop et al, 1993;Calvert et al, 1993;Hickman, 1994;Stephens, 1994;Beaton et al, 1995;Bishop et al, 1996;McLaren et al, 1996;Stedman, 1996;Zhang et al, 1996).…”
Section: Driver Variability And`o -Cycle' Emissionsmentioning
confidence: 99%
“…Nevertheless, the availability of this data has led to widespread use of these laboratory results to predict real-world pollutant levels using emission factor models such as EMFAC (California Air Resources Board) and MOBILE (U.S. EPA). Recent ®eld studies of actual emissions via tunnel studies (Pierson et al, 1990;McLaren et al, 1996), roadside point sampling, across-the-road remote sensing (Lawson et al, 1990;Bishop et al, 1993;Stephens, 1994;Stedman, 1996;Woods, 1996;Zhang et al, 1996), and instrumented vehicles (Schurmann and Staab, 1990;Kelly and Groblicki, 1993;Guenther et al, 1996) have noted the inadequacies of using laboratory data to estimate real-world pollutant levels. These inadequacies are generally attributed to factors such as the limitations of the test driving cycle, vehicle tampering, poor vehicle maintenance, and the high frequency of`o -cycle' driving events under actual driving conditions (Black, 1991;Ross, 1994).…”
Section: Quantifying Real-world Automobile Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Share autos running with more than allotted capacity consume more fuel resulting in higher emissions [2][3][4] . Inadequate maintenance of vehicles enhances emission from them [5][6][7][8][9] . Besides, lack of controlling devices like catalytic converters and filters makes them even larger emitters of pollutants, especially soot particles.…”
mentioning
confidence: 99%